A first report of new chemotype of Thymus migricus Klokov&Desj-shost from East Azarbaijan province of Iran - Imani Dizajeyekan, Yousef; Razban Haghighi, Ahmad; Rangavaran, Rasoul (Journal of Agricultural Sciences (Belgrade), 2016)
In order to determine of Thymus migricus volatile compounds,sampling from two regions of East Azerbaijan province located at Northwestern of Iran was performed.After drying the samples at room temperature,the essential oils were taken by hydro distillation method for 2.5 hours.The essential oils were dehydrated over anhydrous sodiumsulfate.Composition of the oils were identified by GC and GC-MS analyses.The eleven and nineidentified compounds from Mishoo and Espiran regions represents 94.62,86.08 total oils compositions, respectively.In Mishoo,the percentage of main compounds were including linalool (65.57%),citronellol (15.63%) and geraniol (2.79%) and in Espiran,were linalool was (46.36%),geraniol (26.74%) geranyl acetate (6.17%).The present chemotype of this species is reported for the first time in East Azarbaijan, Iran.